PEGylation of a TLR2-agonist-based vaccine delivery system improves antigen trafficking and the magnitude of ensuing antibody and CD8+ T cell responses. (August 2017) - Sekiya, Toshiki; Yamagishi, Junya; Gray, John Henry V.; Whitney, Paul G.; Martinelli, Axel; Zeng, Weiguang; Wong, Chinn Yi; Sugimoto, Chihiro; Jackson, David C.; Chua, Brendon Y.
Abstract: The lipopeptide R4 Pam2 Cys is an agonist for toll-like receptor-2 (TLR2), a key pathogen-associated molecular pattern receptor expressed on many antigen-presenting cells such as dendritic cells (DCs). Electrostatic association of R4 Pam2 Cys with soluble protein antigens significantly enhances their immunogenicity and there is evidence to suggest that reducing the size of suitably adjuvanted-antigen complexes in solution may further improve their immunostimulatory capabilities. In this study, we investigated how incorporation of polyethylene glycol (PEG) into R4 Pam2 Cys affects the size, activity and efficacy of formed antigen-lipopeptide complexes. The presence of PEG was shown to increase solubility with a concomitant reduction in the particle size of vaccine formulations that was dependent on the length of PEG used. When compared to non -PEGylated R4 Pam2 Cys, vaccination of animals with antigen-complexed PEGylated R4 Pam2 Cys resulted not only in improvements in antibody production but significantly higher antigen-specific CD8 + T cell responses. Both lipopeptides exhibited similar in vitro capabilities to induce DC maturation, facilitate antigen uptake and presentation to T cells. Moreover, analyses of the transcriptomes obtained from DCs treated with either lipopeptide revealed a large number of commonly induced genes with similar transcript expression levels, suggesting that common signalling pathways and processes were engaged following activation by either lipopeptide. In vivo analysis however revealed that vaccination with antigen-complexed PEGylated R4 Pam2 Cys resulted in improved antigen presentation to T cells. These heightened responses were not attributed to prolonged antigen persistence but rather due to more rapid transportation of antigen from the injection site into the draining lymph nodes over a short period of time. Our results indicate that reducing the size of formed antigen-TLR2-agonist complexes by PEGylation does not compromise the activity of the agonist but in fact enhances its trafficking in vivo ultimately leading to improved humoral and cell-mediated immune responses.